A novel biomarker-based prognostic score in acute ischemic stroke: The CoRisk score. (26th March 2019) - De Marchis, Gian Marco; Dankowski, Theresa; König, Inke R.; Fladt, Joachim; Fluri, Felix; Gensicke, Henrik; Foerch, Christian; Findling, Oliver; Kurmann, Rebekka; Fischer, Urs; Luft, Andreas; Buhl, Daniela; et al.
Abstract : Objectives: To derive and externally validate a copeptin-based parsimonious score to predict unfavorable outcome 3 months after an acute ischemic stroke (AIS). Methods: The derivation cohort consisted of patients with AIS enrolled prospectively at the University Hospital Basel, Switzerland. The validation cohort was prospectively enrolled after the derivation cohort at the University Hospital of Bern and University Hospital Basel, Switzerland, as well as Frankfurt a.M., Germany. The score components were copeptin levels, age, NIH Stroke Scale, and recanalization therapy (CoRisk score). Copeptin levels were measured in plasma drawn within 24 hours of AIS and before any recanalization therapy. The primary outcome of disability and death at 3 months was defined as modified Rankin Scale score of 3 to 6. Results: Overall, 1, 102 patients were included in the analysis; the derivation cohort contributed 319 patients, and the validation cohort contributed 783. An unfavorable outcome was observed among 436 patients (40%). For the 3-month prediction of disability and death, the CoRisk score was well calibrated in the validation cohort, for which the area under the receiver operating characteristic curve was 0.819 (95% confidence interval [CI] 0.787–0.849). The calibrated CoRisk score correctly classified 75% of patients (95% CI 72–78). The net reclassification index between the calibrated CoRisk scores with and without copeptin was 46% (95% CI 32–60). Conclusions: The biomarker-based CoRisk score for the prediction of disability and death was externally validated, was well calibrated, and performed better than the same score without copeptin. ClinicalTrials.gov identifier: NCT00390962 (derivation cohort) and NCT00878813 (validation cohort).